96.5k views
0 votes
20r + 11r + –19r − –4 = –20

2 Answers

2 votes

Answer:

r = -2

Explanation:

20r + 11r - 19r + 4 = -20

12r + 4 = -20

subtract 4 from both sides of the equation

12r + 4 - 4 = -20 - 4

12r = -24

divide both sides by 12

12r/12 = -24/12

r = -2

User Anand Soni
by
5.8k points
4 votes

Answer:

r=-2

Explanation:

First, you need to combine like terms so now you have 12r-(-4)=-20. Then you have to subtract -4 to -20 which equals -24 so now you have 12r=-24. Finally, you divide 12 from both sides and you get r=-2

User Kikiwora
by
5.2k points